Resveratrol-induced cytotoxicity in human Burkitt's lymphoma cells is coupled to the unfolded protein response - Yan Ying; Gao Yan-Yan; Liu Bao-Qin; Niu Xiao-Fang; Zhuang Ying; Wang Hua-Qin (BMC Cancer, 2010)
Abstract Background Resveratrol (RES), a natural phytoalexin found at high levels in grapes and red wine, has been shown to induce anti-proliferation and apoptosis of human cancer cell lines. However, the underlying molecular mechanisms are at present only partially understood. Method The effects of RES on activation of unfolded protein responses (UPR) were evaluated using Western blotting, semi-quantitative and real-time RT-PCR. Cell death was evaluated using Annexin V/PI staining and subsequent FACS. Results Similar as tunicamycin, treatment with RES lead to the activation of all 3 branches of the UPR, with early splicing of XBP-1 indicative of IRE1 activation, phosphorylation of eIF2α consistent with ER resident kinase (PERK) activation, activating transcription factor 6 (ATF6) splicing, and increase in expression levels of the downstream molecules GRP78/BiP, GRP94 and CHOP/GADD153 in human Burkitt's lymphoma Raji and Daudi cell lines. RES was shown to induce cell death, which could be attenuated by thwarting upregulation of CHOP. Conclusions Our data suggest that activation of the apoptotic arm of the UPR and its downstream effector CHOP/GADD153 is involved, at least in part, in RES-induced apoptosis in Burkitt's lymphoma cells.